The Danish High-Risk and Resilience Study—VIA 15 – A Study Protocol for the Third Clinical Assessment of a Cohort of 522 Children Born to Parents Diagnosed With Schizophrenia or Bipolar Disorder and Population-Based Controls - Thorup, Anne Amalie Elgaard; Hemager, Nicoline; Bliksted, Vibeke Fuglsang; Greve, Aja Neergaard; Ohland, Jessica; Wilms, Martin; Rohd, Sinnika Birkehøj; Birk, Merete; Bundgaard, Anette Faurskov; Laursen, Andreas Færgemand; Jefsen, Oskar Hougaard; Steffensen, Nanna Lawaetz; et al. (Frontiers in Psychiatry, 2022)
Background Children born to parents with severe mental illness have gained more attention during the last decades due to increasing evidence documenting that these children constitute a population with an increased risk of developing mental illness and other negative life outcomes. Due to high quality research with cohorts of offspring with familial risk and increased knowledge about gene-environment interactions, early interventions and preventive strategies are now being developed all over the world. Adolescence is a period characterised by massive changes, both in terms of physical, neurologic, psychological, social, and behavioral aspects. It is also the period of life with the highest risk of experiencing onset of a mental disorder. Therefore, investigating the impact of various risk and resilience factors in adolescence is important. Method The Danish High Risk and Resilience Study started data collection in 2012, where 522 7-year-old children were enrolled in the first wave of the study, the VIA 7 study. The cohort was identified through Danish registers based on diagnoses of the parents. A total of 202 children had a parent diagnosed with schizophrenia, 120 children had a parent diagnosed with bipolar disorder and 200 children had parents without these diagnoses. At age 11 years, all children were assessed for the second time in the VIA 11 study, with a follow-up retention rate of 89%. A comprehensive assessment battery covering domains of psychopathology, neurocognition, social cognition and behavior, motor development and physical health, genetic analyses, attachment, stress, parental functioning and home environment was carried out at each wave. MRI brain scans and EEG were included from age 11. In this study protocol for the third wave of assessment, The VIA 15 study, participants being 15 years of age and the full, three-day long assessment battery is described including also risk behaviour, magnetoencephalography, sleep and a white noise paradigm. Discussion We will discuss the importance of longitudinal studies and cross-sectional data collection and how studies like this may inform us about unmet needs and windows of opportunity for future preventive interventions, early illness identification, and treatment in the future.